Changes in social relationships during an initial "stay-at-home" phase of the COVID-19 pandemic: A longitudinal survey study in the U.S. (April 2021) - Philpot, Lindsey M.; Ramar, Priya; Roellinger, Daniel L.; Barry, Barbara A.; Sharma, Pravesh; Ebbert, Jon O.
Abstract: Rationale: Severe acute respiratory syndrome Coronavirus 2 (SARS CoV-2), the virus that causes COVID-19, and consequent social distancing directives have been observed to negatively impact social relationships but the impact of these changes on the quality of social relationships at a population level has not been explored. Objective: To evaluate changes in social relationships in a U.S. population sample during a time of social distancing. Methods: We deployed a matched, longitudinal survey design of the National Institutes of Health Adult Social Relationship Scales to assess the social aspects of emotional support, instrumental support, friendship, loneliness, perceived hostility, and perceived rejection from a time without social distancing (February 2018) to a time where social distancing directives were active (May 2020). Changes in social relationships were compared using paired t-tests, and generalized linear regression models were constructed to identify subpopulations experiencing differential changes in each subdomain of social relationships during social distancing. Results: Within our sample population, individuals experienced an increased sense of emotional support, instrumental support, and loneliness, and decreased feelings of friendship and perceived hostility during a period of social distancing. Individuals with low self-rated health experienced a decreased sense of emotional support, and females experienced increased feelings of loneliness compared with males. Conclusions: Social distancing measurably impacts social relationships and may have a disproportionate impact on females and individuals with lower self-rated health. If novel emergent infectious diseases become more commonplace, social interventions may be needed to mitigate the potential adverse impact of social distancing on social relationships. Highlights: Increased emotional and instrumental support emerged during social distancing. Respondents experienced more loneliness and less sense of friendship. Those with poorer health experienced decreased sense of emotional support. Women experienced an increased sense of loneliness compared to men.